2021
DOI: 10.1007/s10342-021-01432-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tree mixture on forest productivity: tree species addition versus substitution

Abstract: 1. Mixture effect on stand productivity is usually apprehended through a substitutive approach, whereby productivity in mixed stands is compared to productivity in monocultures, at equivalent stand density. This approach has proved that in many cases mixed stands perform better than monospecific forests, however, we do not yet have a solid theory about species behaviour in the mixture or even guidelines for combining species. The addition of a second tree species to an existing mono-specific stand has received… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Previous studies at the same experimental site have shown that pines and birches are much taller than oaks because the latter have a lower growth rate (Damien et al 2016;Toïgo et al, 2022). While maritime pines were on average 7.80 m tall in 2016 and birches 6.48 m, oaks were only 1.38 m (Pyrenean oak), 1.42 m (pedunculate oak) and 1.77 m (green oak), that is, similar average height as the understory vegetation 1.03 m (Figure S2).…”
Section: Plot Selectionmentioning
confidence: 99%
“…Previous studies at the same experimental site have shown that pines and birches are much taller than oaks because the latter have a lower growth rate (Damien et al 2016;Toïgo et al, 2022). While maritime pines were on average 7.80 m tall in 2016 and birches 6.48 m, oaks were only 1.38 m (Pyrenean oak), 1.42 m (pedunculate oak) and 1.77 m (green oak), that is, similar average height as the understory vegetation 1.03 m (Figure S2).…”
Section: Plot Selectionmentioning
confidence: 99%
“…A recent study of mixtures of Pinus pinaster and Betula pendula in France found the same effect (Toigo et al, 2022). The addition of the pioneer species (B. pendula) with low demands on soil, water and nutrients can boost the productivity of the whole stand.…”
Section: Discussionmentioning
confidence: 82%
“…Подібна тенденція наявна під час порівняння за матеріалами лісовпорядкування фактичної продуктивності деревостанів із природною (Vorobyov 1959) або потенційною (Turkevich et al 1973, Ostapenko & Tkach 2002, Vedmid & Gavrilov 2004, Tkach et al 2018. Величини середнього запасу на 1 га змінюються внаслідок зміни площі вкритих лісовою рослинністю земель, вікової структури деревостанів та участі деревних порід у складі мішаних деревостанів (Vasiliev 1962, Toïgo et al 2022.…”
unclassified